Printing toner used as carrier for immobilization of laccase. (January 2022) - Li, Xijie; Wang, Juzheng; Feng, Diyi; Huang, Han; Deng, Yuefeng; Yang, Chengli; Ouyang, Jie; Li, Dali; Shi, Ruofu
Abstract: The search for seeking novel immobilized enzyme carriers is a hot topic in the field of enzyme engineering. As a kind of common office consumable, magnetic printing toner has been terribly wasted, leading to potential harm to the environment. We try to use printing toner as carrier for enzyme immobilization to realize waste reuse. In this paper, the laccase extracted from Agaricus bisporus was successfully immobilized on chitosan coated magnetic printing toner by glutaraldehyde linking. The use of printing toner is proved to be feasible. The results show that the optimal temperature of immobilized laccase is 40 °C, and the optimal pH is 3.0. Compared with free laccase, the optimal temperature and optimal pH have been obviously changed after immobilization. And the pH tolerance has been significantly improved, which can remain 53% activity after 5 cycles. Because of the use of magnetic printing toner, it is more convenient to recycle the immobilized enzyme. In this study, printing toner was used as carrier for the immobilization of enzyme and the discarded printing toner recycling was realized. Highlights: The immobilized enzyme carrier with printing toner as the main body was successfully constructed. Laccase was successfully immobilized with the new carrier. The new carrier uses discarded print toner to reduce environmental pollution.